2012
DOI: 10.1021/ja210531q
|View full text |Cite
|
Sign up to set email alerts
|

RNA Unwinding from Reweighted Pulling Simulations

Abstract: The forming and melting of complementary base pairs in RNA duplexes are conformational transitions required to accomplish a plethora of biological functions. Yet the dynamic steps of these transitions have not been quantitatively characterized at the molecular level. In this work, the base opening process was first enforced by atomistic pulling simulations and then analyzed with a novel reweighting scheme which allowed the freeenergy profile along any suitable reaction coordinate, e.g. solvation, to be reconst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 54 publications
3
53
0
Order By: Relevance
“…The existence of the trapped state, which was missed in previous studies (74,75), makes the overall folding process more complex. The kinetics of this elementary folding step cannot be simply described by a two-state process (i.e., the kinetics are multistate).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The existence of the trapped state, which was missed in previous studies (74,75), makes the overall folding process more complex. The kinetics of this elementary folding step cannot be simply described by a two-state process (i.e., the kinetics are multistate).…”
Section: Discussionmentioning
confidence: 93%
“…Previous pulling simulations suggested that a 3′-base is more stable than its 5′-base pairing partner. In a folding reaction, the 3′-base is likely to fold first through single-stranded base stacking, followed by folding of the 5′-base through base pairing with the 3′-base (75,84,95,96). Here, we focus on the second step, namely, the folding kinetics of the 5′-base (nucleotide G1) after the 3′-base (nucleotide C6) is folded into the native state (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We also stress that being able to reproduce the fluctuations of the bases is by itself an advantage because their functional role is of primary importance in nucleic acids and their dynamics can affect different aspects of the behavior of RNA molecules (see, e.g., Refs. [3,69,78]).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] In the case of RNA folding, a few partly successful atomistic simulations have been reported. [10][11][12][13] However, recent extensive simulations of unstructured oligonucleotides for which converged sampling is affordable have unambiguously shown that current force-field parameters are not accurate enough to reproduce solution experiments.…”
Section: Introductionmentioning
confidence: 99%